Schweigger’s (1812) chelonian types from the extinct eighteenth century Portuguese “Royal cabinet of natural history of Ajuda”: some contributions for their identification and nomenclatural implications - Ceríaco, Luis M. P.; Bour, Roger (Zootaxa, 2012)
The work Prodromus Monographiae Cheloniorum, published by Schweigger in 1812, has recently been the subject ofseveral studies. One result of these studies—the rediscovery of the Testudo gigantea Schweigger, 1812holotype—triggered an intense debate in The Bulletin of Zoological Nomenclature, where, among other issues in dispute,the identity and nature of the specimen indicated as the holotype for the species is put in question. Using historical sources,mostly unpublished, and analysis and comparison of taxidermic characteristics of the specimen with other specimens ofthe same nature, we can clearly trace its origin to the extinct Royal Cabinet of Natural History of Ajuda in Lisbon, fromthe “philosophical journey” of Alexandre Rodrigues Ferreira to the specimens transported to Paris by Geoffroy Saint-Hilaire in 1808, thus helping dispel any doubts regarding the identity and nature of what is being identified as the Testudogigantea holotype, along with other chelonian specimens. This information is of great importance in the current taxonomicdebate as well as in recognizing the historic importance of the Royal Cabinet of Natural History of Ajuda and Geoffroy Saint-Hilaire’s 1808 mission to Lisbon.